1995
DOI: 10.1089/thy.1995.5.81
|View full text |Cite
|
Sign up to set email alerts
|

Possible Limited Bone Loss with Suppressive Thyroxine Therapy Is Unlikely to Have Clinical Relevance

Abstract: To determine the effect of suppressive doses of thyroxine (T4) on bone mass, we studied 50 women on suppressive doses of T4 for 3-27 years (mean of 11 years). Twenty-five had nontoxic goiter and 25 had well-differentiated thyroid carcinoma. Fifty controls were matched for age, menopausal status, and body mass index. Bone mineral density (BMD) was measured in the lumbar spine (LS), femoral neck (FN), trunk (TK), and extremities (EXT) by dual-energy X-ray absorptiometry (DXA). In addition, the trunk area was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
6

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 34 publications
2
46
1
6
Order By: Relevance
“…A number of long-term safety issues surround THST, particularly in growing patients who are likely to receive the modality for a very long time (Muller et al 1995, Shapiro et al 1997, Horne et al 2004, Botella-Carretero et al 2004. Potential THST side effects may include osteoporosis (Schneider & Reiners 2003), and of special concern, cardiovascular complications, particularly ventricular hypertrophy (Biondi et al 1993, Fazio et al 1995, Matuszewska et al 2001).…”
Section: Goal Of Ablation Rationalementioning
confidence: 99%
“…A number of long-term safety issues surround THST, particularly in growing patients who are likely to receive the modality for a very long time (Muller et al 1995, Shapiro et al 1997, Horne et al 2004, Botella-Carretero et al 2004. Potential THST side effects may include osteoporosis (Schneider & Reiners 2003), and of special concern, cardiovascular complications, particularly ventricular hypertrophy (Biondi et al 1993, Fazio et al 1995, Matuszewska et al 2001).…”
Section: Goal Of Ablation Rationalementioning
confidence: 99%
“…Some reports, including a meta-analysis by Wü ster (9), have suggested that the bone mineral density (BMD) is reduced in patients taking long-term treatment to suppress thyroid stimulating hormone (TSH) (levothyroxine, L-T 4 ) compared with controls (10-13). However, other studies have failed to confirm this decremental effect of L-T 4 treatment on BMD (14)(15)(16)(17) or on the prevalence of fracture (18,19). L-T 4 treatment that does not suppress TSH seems to have little effect on bone (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Rezente Studien versuchten eine weitere Differenzierung in Bezug auf die Dosierungen der suppL-T4-Medikation vorzunehmen. In der Studie von Müller et al [63] wurden bei 50 Frauen (25 mit Struma nodosa, 25 mit DTC) die Veränderungen der BMD im Vergleich zu einer euthyreoten Kontrollgruppe untersucht. Die mittlere L-T4 Tagesdosis …”
Section: Opg/rankl Und Schilddrüseunclassified
“…In der Studie von Toivonen et al [69] erhielten die Patienten 215 µg L-T4/d; ein Unterschied der BMD zwischen L-T4 therapierten Patienten und Kontrollpersonen konnte nicht festgestellt werden. In der Publikation von Müller et al [63] war die mittlere L-T4 Tagesdosis bei Strumapatientinnen 150 µg/d, bei Patientinnen mit DTC 230 µg/d. Nur bei Patientinnen mit DTC konnte ein gerade signifikanter BMD Verlust von 5 % an den Extremitäten erhoben werden.…”
Section: Bmd Und Knochenstoffwechsel In Abhängigkeit Der Tagesdosisunclassified